2020
DOI: 10.1016/j.fochx.2019.100072
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hybrid yeasts on the aroma profile of cool climate Riesling wines

Abstract: HighlightsFor the first time a study reports about hybrids yeast influence on Riesling wine.For the first time a study compares different commercial hybrids yeast.For the first time several specific aroma compounds are studied for hybrids yeast.Some non volatile compounds are studied for hybrids yeast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
(46 reference statements)
1
12
0
1
Order By: Relevance
“…Alcohol not detected in the 'must' at Day 0 is consistent with several reports on wine making from different researchers [12,18,32,34]. Kanter et al [37] had also reported that fermentation of wine by hybrid yeast, S. cerevisiae × S. paradoxus (SC × SP was completed on day 14.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Alcohol not detected in the 'must' at Day 0 is consistent with several reports on wine making from different researchers [12,18,32,34]. Kanter et al [37] had also reported that fermentation of wine by hybrid yeast, S. cerevisiae × S. paradoxus (SC × SP was completed on day 14.…”
Section: Discussionsupporting
confidence: 87%
“…According to Kanter et al [37], yeast and its metabolic products are essentially responsible for the development of preferred sensory properties in wines. This has endeared more people to prefer alcoholic wines to other products.…”
Section: Introductionmentioning
confidence: 99%
“…A pH 526 pH-meter equipped with a SennTix 81 electrode (WTW, Waldböckelheim, Germany) was used to measure the pH. Measurements of the non-volatile organic acids, ethanol, and residual sugars were performed by high-performance liquid chromatography (HPLC) according to Kanter et al, 2020 [ 26 ]. For the analyses of the esters, higher alcohols, and fatty acids, the method of the Department of Microbiology and Biochemistry of Hochschule Geisenheim University [ 27 ] was applied.…”
Section: Methodsmentioning
confidence: 99%
“…There have been a few efforts to cross in useful traits for production of beer ( Nikulin et al, 2018 ) and biofuels ( Benjaphokee et al, 2012 ), and the wine industry in particular has used crossing, with a particular emphasis on interspecific hybridization with other Saccharomyces species. Hybrid crosses have been utilized in the wine industry to impart new flavors/aromas ( Bellon et al, 2011 , 2013 ; Kanter et al, 2019 ) and freeze-tolerance ( Kishimoto, 1994 ; Zambonelli et al, 1997 ; Sipiczki, 2008 ; Pérez-Través et al, 2012 ), although these hybrids are typically sterile. New genetic editing techniques that allow for the successful completion of meiosis in normally sterile hybrids ( Bozdag et al, 2019 ) is a promising development for the future use of interspecific hybrids in industry.…”
Section: Future Needsmentioning
confidence: 99%